Search for Pair-Produced Resonances Each Decaying into at Least Four Quarks in Proton-Proton Collisions at root s=13 TeV - (:unkn) unknown (AMER PHYSICAL SOC, 2018)
This Letter presents the results of a search for pair-produced particles of masses above 100 GeV that each decay into at least four quarks. Using data collected by the CMS experiment at the LHC in 2015-2016, corresponding to an integrated luminosity of 38.2 fb(-1), reconstructed particles are clustered into two large jets of similar mass, each consistent with four-parton substructure. No statistically significant excess of data over the background prediction is observed in the distribution of average jet mass. Pair-produced squarks with dominant hadronic R-parity-violating decays into four quarks and with masses between 0.10 and 0.72 TeV are excluded at 95% confidence level. Similarly, pair-produced gluinos that decay into five quarks are also excluded with masses between 0.10 and 1.41 TeV at 95% confidence level. These are the first constraints that have been placed on pair-produced particles with masses below 400 GeV that decay into four or five quarks, bridging a significant gap in the coverage of R-parity-violating supersymmetry parameter space.
Keywords: SUPERSYMMETRY; PREDICTIONS; STATES